Augmented Reality Molecular Shape Cards: A Novel Approach to Strengthen Students Understanding of Molecular Shape - Pratama, M Sindy Carolin; Ulfah, Maria; Enawaty, Eny; Williams, Dylan; Erlina, Erlina (Universitas Syiah Kuala, 2025)
Students often face difficulties in visualizing molecular shapes based on the valence shell electron pair repulsion (VSEPR) theory, which is an abstract concept in chemistry. To address this issue, instructional materials need to be developed to help students visualize molecular shapes more concretely. This study uses the research and development (RD) method with the 4D (define, design, develop, and disseminate) development model. The developed instructional materials include cards and an augmented reality (AR) application that allow students to visualize and predict molecular shapes in a tangible way. Validation was conducted by experts in media, content, and language, resulting in feasibility ratings of 98.1% for media aspects, 92.8% for content and language aspects, with an overall average rating of 95.45%. After making improvements to the media, an initial response test was conducted with students, yielding an average score of 90.5% with an excellent rating, and a main scale response test showed a percentage of 96.9%, also categorized as excellent. Based on the feasibility and response tests, the molecular shape cards (MoSCa) media is ready to be implemented in the learning process. The student responses to the initial scale test were 90.5%, and to the main scale test were 96.9%, both rated as excellent. The results indicate that the MoSCa media, based on augmented reality, is engaging and effectively supports students' understanding of molecular shape concepts